Study on multiple wind turbines in a platform under extreme waves and wind loads - Shen-Haw Ju; Yi-Chen Huang (Energy Conversion and Management: X)
The integration of multiple floating wind turbines poses complex challenges, particularly under large wave loads. This study analyzed the Floating Offshore Wind Turbine (FOWT) platform with multiple wind turbines, which integrates OpenFAST with Newmark’s finite element analysis. A novel method for calculating the floating stiffness and member forces of beam elements was developed and validated, thereby demonstrating both accuracy and efficiency. Key findings include the effective performance of the yaw system in automatically aligning with the wind direction, significantly reducing rotor blade-induced wind loads, especially in dynamic conditions like tropical cyclones. The analysis also explores the cost implications for FOWT platforms, revealing that while the steel weight per MW power is comparable for platforms with one or two turbines, it increases substantially for three-turbine platforms due to the need for larger and more robust supports. Additionally, increasing the number of turbines can reduce the weight of pontoons and towers, yet this advantage is tempered by the increased weight of the connection supports. Therefore, optimizing the balance between platform size and turbine number is crucial for cost-effectiveness and structural integrity.